Application of protective weight-bearing in osteonecrosis of the femoral head: A systematic review and meta-analysis of randomized controlled trials and observational studies - Chen, Wen-huan; Guo, Wen-xuan; Li, Jian-xiong; Wei, Qiu-shi; Li, Zi-qi; He, Wei (Frontiers in Surgery, 2022)
Background: The aim of this systematic review and meta-analysis was to estimate the efficacy and prognostic value of protective weight-bearing for ONFH. Methods: The authors searched the PubMed, EMBASE and Cochrane Library databases, up to February 25, 2022. RCTs and observational studies on conservative treatment, including the use of crutches, for skeletally mature patients with ONFH and written in English were included. Outcomes were the total hip arthroplasty (THA) rate, collapse rate, Hip Harris score (HHS) and visual analog scale (VAS) score. Cochrane Review Manager Software 5.4 and Stata 15.1 were used to perform the statistical analyses. Results: A total of 14 studies involving 813 patients (1025 hips) were included in this meta-analysis. The results showed that the THA rate, collapse rate, HHS and VAS scores in the protective weight-bearing group were not significantly different from those in the surgical group. In the protective weight-bearing group, the results showed that the THA rate was 40%, 8% in ARCO stage II, 37% in ARCO stage III, and the collapse rate was 46%. The mean HHS and VAS score was 80.86 and 1.00, respectively. The HHS score at the 3-, 6-, 12-, and 24-month follow-up was 79.93, 83.94, 85.94, and 96.09 points, respectively, whereas the VAS score at the 6- and 12-month follow-up was 2.20 and 1.29, respectively. Conclusions: Protective weight bearing could achieve satisfactory results in terms of THA rate, collapse rate, HHS and VAS scores. Protective weight-bearing allows most precollapse patients to preserve the hip but also allows postcollapse patients to delay THA or hip-preserving surgery. The effects and prognosis of protective weight-bearing in the short or mid-term are noninferior to surgical hip preservation and are a viable alternative option for osteonecrosis of the femoral head.